ACCESS TO HEALTH AS A FACTOR OF POVERTY - Sukidin, Sukidin; Faridah, Idah; Putri, Rynesa Gresela; Berliana. F, Cantika (Bina Bangsa International Journal of Business and Management, 2024)
Health and poverty are two interconnected issues that form a cycle of cause and effect. Poverty limits access to adequate healthcare services, increasing the risk of diseases and lowering the quality of life. Conversely, poor health exacerbates economic conditions for low-income families through high medical expenses and lost productivity. This article examines the relationship between health and poverty in Indonesia, its impact on societal welfare, and government initiatives such as the National Health Insurance (JKN) program and economic empowerment efforts to break this cycle. Based on a literature review, comprehensive solutions are required to address both issues simultaneously to achieve a healthier and more prosperous society.